Exercised-based cardiac rehabilitation associates with lower all-cause mortality in patients with primary pulmonary hypertension - Kleinnibbelink, Geert; Buckley, Benjamin J. R.; Harrison, Stephanie L.; Williams, Nefyn; Fazio-Eynullayeva, Elnara; Underhill, Paula; van Dijk, Arie P. J.; Lip, Gregory Y. H.; Thijssen, Dick H. J. (Frontiers in Sports and Active Living, 2023)
Background. Despite pharmacological therapies to improve outcomes of pulmonary hypertension (PH), poor long-term survival remains. Exercised-based cCardiac rehabilitation (exCRExCR) may be an alternative strategy to improve prognosis. Therefore, using an electronic medical record (EMR) database, the objective of this study was to compare mortality between patients with primary PH with exCRExCR versus propensity-matched PH patients without exCRExCR.The retrospective analysis was conducted on February 15, 2023 using anonymized data within TriNetX, a global federated health research network. All patients were aged ≥18 years with primary PH recorded in EMRs with at least 1-year follow-up from exCRExCR. Using logistic regression models, patients with PH with an EMR of exCRExCR were 1:1 propensity score-matched with PH patients without exCRExCR for age, sex, race, and comorbidities, and cardiovascular care.Results. In total, 109,73670,875 patients with primary PH met the inclusion criteria for the control group and 637 784 patients with primary PH met the inclusion criteria for the exCRExCR cohort. Using the propensity score-matched cohorts, 1-year mortality from exCRExCR was proportionally lower with 13.69% (n=10187 of 628 744 patients) in the exCRExCR cohort compared to 23.31.0% (n=133 174 of 747632 patients) in the controls (OR 0.5260, 95% CI 0.405-0.6881).The present study of 1,514 patients with primary PH suggests that exCRExCR is associated with 480% lower odds of 1-year mortality, when compared to propensity score-matched patients without exCRExCR.